FEATURES OF TEACHING MUSICAL FOLKLORE AT MUSIC AND PEDAGOGICAL FACULTIES OF UKRAINIAN PEDAGOGICAL UNIVERSITIES (Pedagogy of Higher and Secondary Education, 2007)
This article deals with pedagogical aspects of music and folklore education at the musicpedagogical faculties (institutes) of pedagogical universities. It analyses the meaning of folkorism as an inseparable component of the contents of the subjects taught. They are as follows: special instrument, vocal, choir and orchestra, choir arrangement, ansamble and many others. A comparative analyses of the number of sound folklore material at musicpedagogikal faculties and